Red room temperature phosphorescence of lead halide based coordination polymer showing efficient angle-dependent polarized emission and photoelectric performance. Issue 26 (21st June 2022) - Tian, Xu-Ke; Zhang, Ji-Rui; Wen, Meng-Yao; Liu, Zi-Han; Guo, Jia-hui; Ma, Cheng-Yu; Zhang, Hao-Yi; Yang, Xiao-Gang; Ma, Lu-Fang
Abstract : A coordination polymer exhibiting rare example of red room-temperature phosphorescence has been synthesized. The alternating arrangement of electronic donor–acceptor at molecular level enables high electrochemistry and photovoltaic active. Abstract : The development of organic–inorganic hybrid materials with long-lived room temperature phosphorescence (RTP) has attracted tremendous attention owing to their promising applications in the optoelectronic and anti-counterfeiting fields. In this work, by the selection of lead halide and electron-poor heteroaromatic molecule 1, 10-phenanthroline (phen), a coordination polymer [Pb(phen)Cl2 ] has been synthesized under hydrothermal conditions. This complex shows an alternating arrangement of a long-range order of phen π-conjugated systems and lead halide inorganic chains as revealed by X-ray single-crystal structural analysis. This structural character and special chemical components endow this hybrid material with a rare example of red room temperature phosphorescence. Its electronic structure and electronic transition behavior were further examined by theoretical calculations. Meanwhile, the film of the complex features remarkable angle-dependent polarized emission and photoelectric performance.